Duration of the natural infection of the mammary gland by coagulase negative staphylococci in primiparous cows / Duração das infecções naturais da glândula mamaria por estafilococos coagulase negativos em vacas primíparas - Juliana Alves Dias; Rogério Salvador; Lucienne Garcia Pretto-Giordano; Júlio César de Freitas; Ernst Eckehardt Muller; Luís Carlos Vianna (Semina: Ciências Agrárias, 2000)
One hundred fourteen primiparous cows wre analized. They wre from nine milk properties of the west region of São Paulo sate. On the seventh day of lactation. 42 (36.84%) showed infections in 69 (41.07%) quarters. The main aetiologic agents of the intramammary infections on the seventh day were coagulase-negative staphylococci (CMS) with 53,62%, followed by Corynebacterium spp with 26r08% and coagulase-positive staphylococci (CPS), with 11,59% of the positive samples. From the seventh day of lactation on there was a decreasing tendency of the infections by SCN in the previously tnfected mammary quarter (r = 0,63, r2= 0,4) and simultaneously there were new infections by other pathogen in these quarter. On the 150th day, the CNS were not isolated. There was not significant difference (P3 0.05) about the number of infections by udder quarter There was significant difference (P£0rO1) between the average of the somatic cell count (SCC) of the milk samples. It. comes from the infected quarters by SCN (397 x 103/ mL) and of negative quarters (104 x 103/mL).